SARS-CoV-2 Epitope Mapping on Microarrays Highlights Strong Immune-Response to N Protein Region - Angelo Musicò; Roberto Frigerio; Alessandro Mussida; Luisa Barzon; Alessandro Sinigaglia; Silvia Riccetti; Federico Gobbi; Chiara Piubelli; Greta Bergamaschi; Marcella Chiari; Alessandro Gori; Marina Cretich (Vaccines, 2021)
A workflow for rapid SARS-CoV-2 epitope discovery on peptide microarrays is herein reported. The process started with a proteome-wide screening of immunoreactivity based on the use of a high-density microarray followed by a refinement and validation phase on a restricted panel of probes using microarrays with tailored peptide immobilization through a click-based strategy. Progressively larger, independent cohorts of Covid-19 positive sera were tested in the refinement processes, leading to the identification of immunodominant regions on SARS-CoV-2 spike (S), nucleocapsid (N) protein and Orf1ab polyprotein. A summary study testing 50 serum samples highlighted an epitope of the N protein (region 155–71) providing good diagnostic performance in discriminating Covid-19 positive vs. healthy individuals. Using this epitope, 92% sensitivity and 100% specificity were reached for IgG detection in Covid-19 samples, and no cross-reactivity with common cold coronaviruses was detected. Likewise, IgM immunoreactivity in samples collected within the first month after symptoms onset showed discrimination ability. Overall, epitope 155–171 from N protein represents a promising candidate for further development and rapid implementation in serological tests.